Prevalence of diabetes mellitus in outpatients with essential hypertension in China: a cross-sectional study - Liu, Jun (BMJ Publishing Group, 2013)
OBJECTIVES: To investigate the prevalence of diabetes mellitus (DM) and new detection of DM using fasting plasma glucose (FPG) and 2 h plasma glucose (2-hPG) in hypertensive outpatients in China. DESIGN: Multicenter cross-sectional study. SETTING: 46 hospitals in China. PARTICIPANTS: Study patients were consecutively recruited from June to December 2009 from hypertension outpatient clinics in 46 hospitals in 22 provinces, autonomous regions and municipalities in China. At least 100 consecutive patients were recruited in each hospital. FPG was measured for all patients and 2-hPG was measured in those without a history of DM. A total of 4942 hypertensive outpatients aged ≥20 years were included. RESULTS: Prevalence of DM was 24.3% (which included both previously and newly diagnosed cases). Among the 1202 patients with DM, 417 (34.7%) were newly detected. In patients aged <45 years, 52.6% of cases of DM were newly detected. Of the 417 cases of newly detected diabetes, 54.9% were identified using FPG tests and the remaining 45.1% by 2-hPG tests; 27.1% of patients with newly detected DM had FPG <6.1 mmol/L and 16.5% had FPG <5.6 mmol/L. Among the elderly patients (≥65 years), 32.4% had normal FPG (<6.1 mmol/L) and 24.5% had optimal FPG (<5.6 mmol/L). CONCLUSIONS: Our findings showed a high prevalence of DM and newly detected DM among Chinese hypertensive outpatients. Application of additional 2-hPG testing to FPG assay can improve the detection rate of DM, especially in elderly patients.